Time is Power: Aging and Control of Public Space in a Traditional Middle Class Neighborhood in Lima - Pereyra Cáceres, Omar (2016)
In this article, I study the effect of aging of neighbors on local organizations in San Felipe, a middle-class neighborhood in Lima, Peru. I elaborate on this effect by using the case of the control of public space in the neighborhood. I conducted participant observation during a year. During that year, I observed the dynamics of local organizations’ meetings; I interviewed 46 residents of different characteristics; and I observed a large amount of situations andcontroversies among actors in San Felipe’s public space. I find that senior residents are the ones who impose their point of view about the neighborhood’s fortune. This result is surprising considering that senior residents are neither the most numerous group in the neighborhood, neither the one with higher resources. I claim that that happens because senior residents transform time (a scarce resource for young-adult neighbors, though abundant for the seniorneighbors) into organizational power. With that organizational power, senior residents are able to influence on the municipality’s functionaries who not only defend the discourse of senior residents regarding the use of public space, but also transform it according to this discourse.